De-contextualising and Re-contextualising:: Why Mediterranean Archaeology Needs to Get out of the Trench and Back into the Museum - Osborne, Robin (Journal of Mediterranean Archaeology, 2016)
University museums currently play a small part in the research of Mediterranean archaeologists. One major reason for this is that Mediterranean archaeology has become overwhelmingly concerned with understanding objects in the context in which they were found. Museums re-contextualise objects. In this paper I argue that, far from this being a problem, it is an opportunity—an opportunity to escape from the tyranny of the last resting place, of only understanding where objects ended their ancient social lives, and to uncover what artefacts did in their working lives. After a discussion of some extreme means of re-contextualising, two case studies are explored where the idiosyncrasies of university museum collections (the presence of replicas and the random selection of artefacts) are exploited to show how fundamental issues in Mediterranean archaeology can be pursued through such collections. In the first case the juxtaposition of plaster casts of three statues ascribed to the same sculptor or workshop is made to yield a distinctive approach to understanding interactions between gods and men that offers insight into Greek theological assumptions. In the second a peculiarly shaped field for decoration on particular Athenian pots is shown to encourage reflection on a particular aspect of human inter-relations and to have implications not simply for the way pots exercise agency and for the attitudes of painters, but for interpersonal relations in the Mediterranean societies that consumed such pottery.